Searching for Consistency in Attendance Data Recording, Reporting, and Utilization in the USA - Patricia A. Graczyk; Carolyn Gentle-Genitty; Amber Humm Patnode; Sara E. Moulton (Karolinum Press, 2023)
According to the United States Department of Education (USDOE), 16% or over eight million kindergarten through twelfth grade students in the US missed 10% or more school days during the 2017−2018 school year. This is approximately 18 of 180 days required. We know this because schools are mandated to report their attendance data to their respective states and to the USDOE. There are concerns around accuracy and consistency because each state is allowed to compile data in their own way and report only select metrics to the USDOE to comply with federal guidelines. The consistency on federal metrics, nonetheless, allows for similar analyses at the federal and state levels and comparisons across states. To best understand what is reported, we report on data compiled by the National Center for Education Statistics (NCES) housed in the Institute of Education Sciences, the science branch of the USDOE, and describe how attendance data are collected, reported, and used at the national level. We share similar findings for two representative US states − Connecticut and Indiana − to highlight similarities and differences between them, and their "best practices." Key results from these multiple levels of analyses are then discussed, with the goal of informing research, practice, and policy related to school attendance, so that students of all ages and from all backgrounds are provided the opportunity to obtain optimal benefits from schooling throughout their school careers.